(untitled) - Steve Moritsugu (Indianapolis, Indiana, 1998)
The book covers all the standard UNIX commands, useful options, scripts, programming languages like awk and perl, and major variations found in today's UNIX systems. It covers all types of UNIX systems including AIX, BSD, HP-UX, Linux, SCO UNIX, SVR3, SVR4, and UNIXWare - providing enhanced coverage of Sun Solaris 2.x and SunOS 5.x
Keywords: free computer software,operating systems ( computers ),shareware ( computer software ),unix ( computer file )